Chitosan oligosaccharide-based dual pH responsive nano-micelles for targeted delivery of hydrophobic drugs. (1st November 2019) - Wang, Yulong; Khan, Avik; Liu, Yanxin; Feng, Jing; Dai, Lei; Wang, Guanhua; Alam, Nur; Tong, Li; Ni, Yonghao
Highlights: Novel COS-based dual pH responsive nano-micelles (DPRNs) were prepared. Hydrophobic anticancer drugs were encapsulated into water-soluble DPRNs. Results indicate the release of loaded genistein at the intracellular pH. The synthesized DPRNs have great potential for cancer therapy. Abstract: In this study, chitosan oligosaccharide (COS)-vanillin imine (COS-Vani Imine)-based dual pH responsive nano-micelles (DPRNs) were synthesized. The resultant DPRNs were used for encapsulating genistein and its ultimate release upon pH change. The overall concept of DPRNs for the targeted delivery of hydrophobic anticancer drugs was successfully demonstrated. The DPRNs were spherical in shape, nanoscale in dimension (71.2–163.4 nm), with dual pH response. The encapsulation/loading of genistein into DPRNs was achieved and the resultant genistein-loaded DPRNs were stable under the physiological pH (˜7.4); under the cancer cell extracellular pH (˜6.8), the amino groups in COS is protonated, thus becoming positively charged, facilitating their adsorption onto negatively charged cancer cells. Under the cancer cell intracellular pH (˜5.0), the genistein-loaded DPRNs were destroyed as a result of the cleavage of pH sensitive benzoic imine, thereby releasing the loaded genistein.